Hydraulic Driving System of Solar Collector Based on Deep Learning - Wang, Yulin (Big Data Analytics for Cyber-Physical System in Smart City, 2021)
Renewable energy refers to the energy that can be regenerated by raw materials, such as hydropower, wind power, solar energy, biological consumption (biogas), and ocean tide energy. This paper introduces the operation conditions and design scheme of the hydraulic driving system of the solar photothermal power collector. With the strengthening of global environmental protection, researchers all over the world are committed to the utilization and research of renewable energy. For China, coal is the main energy production structure for a long time, and the problems of energy shortage and environmental pollution have become increasingly prominent, which have become two major problems restricting the sustainable development of China’s economy. Therefore, it is advocated to optimize the energy structure and vigorously develop renewable energy such as solar energy.